2020
DOI: 10.1007/s13300-020-00791-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality and Diabetes: A Commentary

Abstract: Socioeconomic inequality of access to healthcare is seen across the spectrum of healthcare, including diabetes. Health inequalities are defined as the 'preventable, unfair and unjust differences in health status between groups, populations or individuals that arise from the unequal distribution of social, environmental and economic conditions within societies, which determine the risk of people getting ill, their ability to prevent sickness or opportunities to take action and access treatment when ill health o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 25 publications
1
46
0
2
Order By: Relevance
“…23 As shown here, the favorable TIR effects of the COVID-19 pandemic accrued disproportionately to patients in areas with relatively high median household income and to early adopters/long-term users of the G6 System. Social inequalities in diabetes care 24 may be related to the diffusion of innovative diabetes technologies such as rtCGM. 25 …”
Section: Discussionmentioning
confidence: 99%
“…23 As shown here, the favorable TIR effects of the COVID-19 pandemic accrued disproportionately to patients in areas with relatively high median household income and to early adopters/long-term users of the G6 System. Social inequalities in diabetes care 24 may be related to the diffusion of innovative diabetes technologies such as rtCGM. 25 …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that flash monitoring use is substantially lower in those with the highest levels of deprivation, 8 even in the context of universal NHS funding, and this was replicated in the current study. A similarly sharp gradient exists with respect to deprivation and CSII use 10 . Clinician preconceptions, with little supporting evidence, relating to who is likely to derive benefit from CSII, may contribute to the inequitable distribution of CSII use 20 .…”
Section: Discussionmentioning
confidence: 99%
“…C‐peptide data were available in 1661 individuals. Flash monitoring has been available on NHS prescription in our centre since February 2018 and the criteria governing eligibility are described in more detail elsewhere 10 . This project did not involve deviation from usual clinical care or access to data beyond our usual clinical IT systems and ethical approval was not required.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond policy change for reimbursement of health technologies such as CGM, disparities in access to health technologies continue to exist when access to diabetes specialists and diabetes educators is limited in areas of socioeconomic deprivation. 59 Second, by virtue of their forward-looking orientation, the capital markets and investment community have already moved forward in assigning winners and losers in the post-COVID-19 world. The winners are indisputably companies and organizations that place technology at the center of what they do-consider that over the past year, at the time of this writing, the S&P Technology Index is up 44% while the S&P 500 overall index is up 18%, and that all of the equity market growth this year has been driven by large-cap technology companies.…”
Section: Covid-19 and Health Economics S-17mentioning
confidence: 99%